2000
DOI: 10.4049/jimmunol.165.11.6590
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell-Derived Factor-1-CXC Chemokine Receptor 4 Interactions Play a Central Role in CD4+ T Cell Accumulation in Rheumatoid Arthritis Synovium

Abstract: Rheumatoid arthritis (RA) is characterized by the accumulation of CD4+ memory T cells in the inflamed synovium. To address the mechanism, we analyzed chemokine receptor expression and found that the frequency of CXC chemokine receptor (CXCR)4 expressing synovial tissue CD4+ memory T cells was significantly elevated. CXCR4 expression could be enhanced by IL-15, whereas stromal cell-derived factor (SDF)-1, the ligand of CXCR4, was expressed in the RA synovium and could be increased by CD40 stimulation. SDF-1 sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
340
1
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(366 citation statements)
references
References 67 publications
22
340
1
3
Order By: Relevance
“…Nanki and colleagues demonstrated that CD40 ligation induces increased expression of SDF-1␣/CXCL12 in RA ST fibroblasts (9). Conversely, Hitchon et al reported that hypoxiainducible factor 1␣ (HIF-1␣) and VEGF enhanced expression of SDF-1␣/CXCL12 mRNA in RA ST fibroblasts, although they did not demonstrate induction of SDF-1␣/CXCL12 protein by TNF␣ or IL-1␤ in RA ST fibroblasts (38).…”
Section: Il-18 and Angiogenic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanki and colleagues demonstrated that CD40 ligation induces increased expression of SDF-1␣/CXCL12 in RA ST fibroblasts (9). Conversely, Hitchon et al reported that hypoxiainducible factor 1␣ (HIF-1␣) and VEGF enhanced expression of SDF-1␣/CXCL12 mRNA in RA ST fibroblasts, although they did not demonstrate induction of SDF-1␣/CXCL12 protein by TNF␣ or IL-1␤ in RA ST fibroblasts (38).…”
Section: Il-18 and Angiogenic Factorsmentioning
confidence: 99%
“…SDF-1␣/CXCL12 plays an important role in the pathogenesis of RA, in that it mediates homing of leukocytes to RA ST and causes the release of matrix metalloproteinase 3 (MMP-3) by chondrocytes (8,9). SDF-1␣/CXCL12 increases the migration and survival of B and T cells in vitro, and exogenous SDF-1␣/CXCL12 increases monocyte migration in a dosedependent manner in a SCID/RA ST chimera model (9,10). Moreover, an antagonist of CXCR4 (a receptor for SDF-1␣/CXCL12) ameliorates arthritis in murine CIA (11).…”
mentioning
confidence: 99%
“…Other investigators have also demonstrated that CD68ϩ synovial macrophage lineage cells as well as fibroblast-like synoviocytes (FLS) express CD40 (8,9). The ligation of CD40 augments the production of IL-12 in synovial cells and synovial fluid macrophages from RA patients (10,11) and enhances the expression of CD54, CD106, IL-6 (12), stromal cell-derived factor 1 (13), and vascular endothelial cell growth factor (14). In vivo, treatment with a monoclonal antibody (mAb) against CD154 prevents the development of type II collagen-induced arthritis in mice (15).…”
mentioning
confidence: 99%
“…31 Additionally, the administration of anti-SDF-1 antibody prevented the development of autoantibodies, nephritis, and death in a murine model of lupus. 32 The expression of SDF-1, which is capable of inducing lymphocyte migration to lymphoid organs, 33 is increased in chronically inflamed tissues such as rheumatoid arthritis synovium, [34][35][36] and the thyroid gland from patients with autoimmune thyroid disease. 22 On the basis of a wide expression of SDF-1 in rheumatoid arthritis synovium, several studies demonstrated that SDF-1 and its receptor CXCR4 are involved in CD4 þ and CD8 þ T-cell 34,35 and CD68 þ monocyte/macrophage 36 migration to and retention in rheumatoid arthritis synovium.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…32 The expression of SDF-1, which is capable of inducing lymphocyte migration to lymphoid organs, 33 is increased in chronically inflamed tissues such as rheumatoid arthritis synovium, [34][35][36] and the thyroid gland from patients with autoimmune thyroid disease. 22 On the basis of a wide expression of SDF-1 in rheumatoid arthritis synovium, several studies demonstrated that SDF-1 and its receptor CXCR4 are involved in CD4 þ and CD8 þ T-cell 34,35 and CD68 þ monocyte/macrophage 36 migration to and retention in rheumatoid arthritis synovium. The expression of SDF-1 by monocytes/macrophages and endothelial cells in SO agrees with immunolocalization studies in rheumatoid arthritis synovium, 36 and suggests a pathogenic role of SDF-1 in the recruitment of leucocytes including B lymphocytes into the eye.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%